Evaluación de los procesos administrativos frente a la eficiencia institucional de la unidad educativa Juan Abel Echeverría. Propuesta de un manual alternativo - Moya Herrera, Max Henry (2016)
This research work has as its theme Administrative processes Assessment against institutional efficiency of the “Juan Abel Echeverria Educational Unit. Proposal of an Alternative Manual", the main objective was to design an alternative manual administrative processes to achieve institutional efficiency, for which instruments that collect relevant information on the subject as polls aimed were applied at the educational community of the institution, where shortcomings in knowledge of administrative processes was made evident, because most respondents were unaware of the rules, policies and procedures of the different departments, areas, commissions, and others of the institution; since it is not updated and has not been properly socialized to the members of the unit; this investigation is considered significant then, it allows administrative, teachers, students and parents to know enough about the administrative processes that achieve institutional efficiency; against it an alternative manual processes imperatives as a proposed solution was developed to reach institutional efficiency with which the administrative may have a supporting document that would facilitate their administrative actions, investigated contents secure updated information that guide effectively the development of the proposed theme and can serve as a source of advice to anyone interested in the subject.